Proactivity of students - between diagnostic assumptions and methodical solutions - Rosalska, Małgorzata; Wierzbicki, Jakub (Adult Education Discourses, 2022)
The aim of this article is to indicate selected possibilities of analysing the construct of proactivity. This goal was achieved by referring to selected definitions and the concepts of proactivity and by discussing a research project aimed at recognizing the proactivity of students towards their professional career. To measure the level of proactivity, the Scale of Proactive Behavior in Career was used, which includes four types of proactivity: general, cognitive, in building a support network and in building psychological comfort. The independent variables in the research were: taking on professional activity during studies, using services offered by a Career Office and a career counsellor. 271 students from four Polish universities took part in the study. The highest mean score was on the general proactivity scale, followed by the proactivity scale in building a support network, the scale of proactivity in building psychological comfort, and the lowest on the scale of cognitive proactivity. These means differ statistically. The conducted analysis also proved that the level of proactivity is statistically significantly differentiated depending on whether the respondents used the Career Office or a career counsellor. The conclusions from the analysis were discussed in two perspectives – diagnostic and methodical.